2009
DOI: 10.3844/jssp.2009.332.341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Infrastructural Facilities on the Rental Values of Residential Property

Abstract: Problem statement: Real estate developers were consistently faced with the issue of making decisions on the types of property to invest their hard earned income or highly competitive secured mortgage funds, which were attached with high lending rates. One of the different sectors that are begging for such investment is residential property development. Approach: This study evaluated the effects of available infrastructure in residential property on its rental values in Akure, Ondo state, Nigeria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 4 publications
2
30
0
1
Order By: Relevance
“…According to Melnikas (1998) and Olujimi and Bello (2009), housing facilities can be defined as rooms furnished with sophisticated amenities, suitable to house social activities and indicative of a certain lifestyle. The major need addressed by such facilities is a dwelling, but we also argue that the desire to interact and socialize with friends or to attain a desired social status may explain why individuals demand some housing facilities.…”
Section: Student Housing Facilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Melnikas (1998) and Olujimi and Bello (2009), housing facilities can be defined as rooms furnished with sophisticated amenities, suitable to house social activities and indicative of a certain lifestyle. The major need addressed by such facilities is a dwelling, but we also argue that the desire to interact and socialize with friends or to attain a desired social status may explain why individuals demand some housing facilities.…”
Section: Student Housing Facilitiesmentioning
confidence: 99%
“…A good pantry must be included in student housing to create a home-like environment. Few researchers clinch that equipping this facility is an inevitable (Olujimi and Bello, 2009;Taha and Sulaiman, 2010). The results shown in Table 3 indicate that the students have ambivalent feelings about the provided pantry.…”
Section: Pantrymentioning
confidence: 99%
See 1 more Smart Citation
“…To Selim, the type of house, type of building, number of rooms, size, and other structural characteristics such as water system, pool, natural gas were the major determinants of house rental values (Selim, 2008). Olujimi& Bello (2009) evaluated the availability and effect of infrastructure on rental values in residential property in Nigeria, particularly in the Akure of the Ondo State. The study utilized the hedonic approach based on regression analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that, 30.5% of rental values of residential buildings were attributed to infrastructural facilities particularly the provision of wall-fence and windows with burglar proof. Subsequently, they recommended that for residential properties to command competitive rental values, amenities likewall-fence and windows with burglar proof amongothers should be provided (Olujimi & Bello, 2009). Larsen (2010) reported on a study to determine whether investors pay less for single-family houses than do buyer/residents.…”
Section: Literature Reviewmentioning
confidence: 99%